The Effect of Okra Seed (Abelmoschus esculentus) Powder Supplementation on Nutritional, Textural, Microstructural, and Sensory Properties of Gluten-Free Muffins - Altan Sahan; Ezgi Ozgoren Capraz (Journal of Food Quality)
Celiac disease is an autoimmune-mediated systemic disorder that develops in those who are genetically predisposed, the management of which is limited to a lifelong gluten-free diet. Gluten-free foods contain fewer proteins, dietary fiber, and minerals than their gluten counterparts. Among the appropriate ingredients, okra seed is known for its high protein, fat, and dietary fiber content, its well-balanced amino acid composition, and its rich unsaturated fatty acid profile. In the present study, muffins were prepared with part of the rice flour substituted by okra seed powder (OSP) (15, 30, and 45%) and the nutritional, textural, microstructural, and sensory properties of the gluten-free muffins were evaluated. The most preferred formulation was determined using the integrated SWARA-TOPSIS multicriteria decision-making method, revealing the 30% OSP-added muffin to be the optimum alternative, with 2.43% ash, 28.01% fat, 10.0% protein, 7.39% total dietary fiber, and 49.75 mg GAE/100 g total phenolic content. In a mineral matter analysis, the Mg, P, K, Ca, Mn, Fe, and Zn contents of the 30% OSP-added sample were found to be 4.3, 1.2, 2.3, 2.7, 1.4, 4.9, and 2.0 times higher than the control sample, respectively. The OSP-added gluten-free muffin samples were also found to be an important source of essential and nonessential amino acids and a good source of linoleic and oleic acids. All of the muffin samples received acceptable sensory scores (>4/7). A texture profile analysis revealed that the hardness, adhesiveness, gumminess, and chewiness values of the muffins increased with the supplementation of OSP, while scanning electron microscope imaging revealed a homogeneous pore structure in the control samples that decreased as the OSP substitution rate increased. The results of the study revealed OSP to be an appropriate natural source of protein and dietary fiber in gluten-free muffin production.